2020
DOI: 10.3390/ani10081339
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status and Liver Function of Young Turkeys Receiving a Diet with Full-Fat Insect Meal from Hermetia illucens

Abstract: We hypothesized that full-fat insect meal from Hermetia illucens (HI) larvae can be an acceptable source of protein and energy in the diet of young turkeys, in an amount adapted to the nutritional needs of these birds, and at the same time can improve their antioxidant status and metabolism. The turkeys were fed a control diet (HI0) without the insect meal, and three diets with increasing HI content of 5%, 10% and 15% (treatments HI5, HI10 and HI15, respectively). The use of 10% or 15% HI in the diet of young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Józefiak and Engberg [ 39 ] demonstrated that the intestinal absorption of diets containing insect protein may be compromised in broiler chickens, because insects are a potential source of peptides with biological activities against gastrointestinal microbiota. In contrast to Dabbou et al [ 12 ], who observed that the FCR was negatively affected even when defatted HI larvae meal was included in broiler chicken diets at 15%, Ognik et al [ 40 ] found that diets containing 15% HI meal had a beneficial influence on the FCR in young turkeys. In the present study, high inclusion rates of full-fat HI larvae meal (50% and 75%) did not compromise the FCR (1–42 d, Table 3 ) except in group HI100, where SBM was completely replaced with HI larvae meal.…”
Section: Discussionmentioning
confidence: 93%
“…Józefiak and Engberg [ 39 ] demonstrated that the intestinal absorption of diets containing insect protein may be compromised in broiler chickens, because insects are a potential source of peptides with biological activities against gastrointestinal microbiota. In contrast to Dabbou et al [ 12 ], who observed that the FCR was negatively affected even when defatted HI larvae meal was included in broiler chicken diets at 15%, Ognik et al [ 40 ] found that diets containing 15% HI meal had a beneficial influence on the FCR in young turkeys. In the present study, high inclusion rates of full-fat HI larvae meal (50% and 75%) did not compromise the FCR (1–42 d, Table 3 ) except in group HI100, where SBM was completely replaced with HI larvae meal.…”
Section: Discussionmentioning
confidence: 93%
“…In this regard [ 76 ], reports a high oleic and palmitic acid content in Tenebrio molitor and Acheta domesticus . In comparison, Hermetia illucens is characterized by a high lauric acid content and a medium-SFA [ 77 ]. Additionally, the ratio of UFAs to SFAs influences some biological activities, as suggested by Ref.…”
Section: Lipidsmentioning
confidence: 99%
“…Reviews on the nutritional value of certain insects, such as black soldier fly larvae, housefly maggot and pupae, mealworms, silkworm pupae, locusts, beetles, grasshoppers, and crickets, show that they have the potential to be used as an alternative protein source in various livestock feeds [ 6 , 7 ]. Additionally, insect meals can be used effectively in rearing of animals, such as poultry, to enhance animal health, intestinal morphology, and the composition of the intestinal microbiota [ 8 ], with an effect close to that of plant bioactive substances [ 9 ]. These insects’ gut microbiota comprises a diverse range of microorganisms that produce bioactive compounds that, among other things, protect their host from pathogenic assault [ 10 ].…”
Section: Introductionmentioning
confidence: 99%